Genomic and pathogenicity islands of Listeria monocytogenes—overview of selected aspects - Natalia Wiktorczyk-Kapischke; Krzysztof Skowron; Ewa Wałecka-Zacharska (Frontiers in Molecular Biosciences, 2023)
Listeria monocytogenes causes listeriosis, a disease characterized by a high mortality rate (up to 30%). Since the pathogen is highly tolerant to changing conditions (high and low temperature, wide pH range, low availability of nutrients), it is widespread in the environment, e.g., water, soil, or food. L. monocytogenes possess a number of genes that determine its high virulence potential, i.e., genes involved in the intracellular cycle (e.g., prfA, hly, plcA, plcB, inlA, inlB), response to stress conditions (e.g., sigB, gadA, caspD, clpB, lmo1138), biofilm formation (e.g., agr, luxS), or resistance to disinfectants (e.g., emrELm, bcrABC, mdrL). Some genes are organized into genomic and pathogenicity islands. The islands LIPI-1 and LIPI-3 contain genes related to the infectious life cycle and survival in the food processing environment, while LGI-1 and LGI-2 potentially ensure survival and durability in the production environment. Researchers constantly have been searching for new genes determining the virulence of L. monocytogenes. Understanding the virulence potential of L. monocytogenes is an important element of public health protection, as highly pathogenic strains may be associated with outbreaks and the severity of listeriosis. This review summarizes the selected aspects of L. monocytogenes genomic and pathogenicity islands, and the importance of whole genome sequencing for epidemiological purposes.